Characterisation and properties of magnetron sputtered nanoscale bi‐layered Ni/Ti thin films and effect of annealing. (August 2015) - Behera, Ajit; Aich, Shampa
<x xml:space="preserve">Abstract</x> Single‐bi‐layer of Ni–Ti thin film was deposited using DC and RF magnetron sputtering technique by layer‐wise deposition of Ni and Ti on Si(100) substrate in the order of Ni as the bottom layer and Ti as the top layer. The deposition of these amorphous as‐deposited thin films was followed by annealing at 300 °C, 400 °C, 500 °C, and 600 °C temperature with 1‐h annealing time for each to achieve crystalline thin films. This paper describes the fabrication processes and the novel characterization techniques of the as‐deposited as well as the annealed thin films. Microstructures were analysed using FESEM and HRTEM. Nano‐indentation and AFM were carried out to characterize the mechanical properties and surface profiles of the films. It was found that, for the annealing temperatures of 300 °C to 600 °C, the increase in annealing temperature resulted in gradual increase in atomic‐cluster coarsening with improved ad‐atom mobility. Phase analyses, performed by GIXRD, showed the development of silicide phases and intermetallic compounds. Cross‐sectional micrographs exhibited the inter‐diffusion between the two‐layer constituents, especially at higher temperatures, which resulted either in amorphization or in crystallization after annealing at temperatures above 400 °C. Copyright © 2015 John Wiley & Sons, Ltd.